PENGARUH SUMBER DAYA, DATA, LINGKUNGAN, KETIDAKPASTIAN, KERANGKA ORGANISASI, DAN KOORDINASI TERHADAP PERENCANAAN MITIGASI DAN ADAPTASI PERUBAHAN IKLIM - Ni Made Putri Pena (Universitas Tribhuwana Tunggadewi, 2015)
The purpose of this study was to describe the influence of resources, data, environment, uncertainty, organizational framework, and the coordination on planning of mitigation and adaptation to climate change in Batu City, either partially or simultaneously. This study uses quantitative methods, with a census approach, with the intention of explanation (explanatory research). Data were analyzed using descriptive statistical analysis techniques and multiple linear regression. The results showed that the resources, data, environment, uncertainty, organizational framework, and coordination, both simultaneously and partially has positive and significant influence on the planning of mitigation and adaptation to climate change in Batu City except uncertainty. Such factors that influence planning should be carefully considered and mapped so it can produce a good planning and the impact of climate change may soon be minimized.